Normal range and genetic analysis of coagulation factor XII in the general Chinese population. Issue 2 (August 2015) - Han, Yanxin; Zhu, Tienan; Jiao, Li; Hua, Baolai; Cai, Huacong; Zhao, Yongqiang
Abstract Background It has been reported that the average activity of coagulation factor XII depends on the ethnicity of the population under study but little information is available on Chinese. We here provide an analysis of the range of activities and antigenic levels of factor XII in healthy Han Chinese and correlate the measurements with polymorphisms and mutations in the corresponding gene. Methods Plasma samples were obtained from 549 healthy Chinese adults (264 men, 285 women; age 16–79 years) undergoing routine check-ups. The samples were subjected to an activated partial thromboplastin time-based factor XII activity assay as well as an enzyme-linked immunosorbent assay. Partial gene sequence analyses were performed in subjects with low factor XII activity and in normal controls. Results Ninety-five percent of the subjects had factor XII activities between 47% and 160.25%, with no evidence for an influence of sex or age. Among 15 subjects with activity levels ≤ 47%, we found one novel nonsense and two missense mutations that may lead to dysfunctional proteins. No mutations were found in a selection of subjects with activities above 47%. Interestingly, however, the particular sequence at a known C/T polymorphism at position 46 just upstream of the translational start codon was correlated with factor XII activity. Subjects homozygous for the T allele, which has an allelic frequency of 0.69, showed significantly lower factor XII activities compared to subjects homozygous for the C allele or those heterozygous for C/T. Conclusions The survey determined the normal range of factor XII activities in healthy Chinese and identified mutations as well as a biased representation of a polymorphic nucleotide in subjects with abnormally low activities. The results provide an essential basis for the diagnosis of FXII deficiencies in Chinese.